Reflex-like spatial updating can be adapted without any sensory conflict - Riecke, B. E.; Beykirch, K.; Bülthoff, H. H. (Perception 32 ECVP Abstract Suplement, 2003)
Reflex-like processes are normally recalibrated with a concurrent sensory conflict. Here, we investigated reflex-like (obligatory) spatial updating (online updating of our egocentric spatial reference frame during self-motion, which is largely beyond conscious control). Our object was to adapt vestibularly induced reflex-like spatial updating with the use of a purely cognitive interpretation of the angle turned--that is, without any concurrent sensory conflict, just by presenting an image with a different orientation, after physical turns in complete darkness. The experiments consisted of an identical pre-test and post-test, and an adaptation phase in between. In all three phases, spatial updating was quantified by behavioural measurements of the new post-rotation orientations (rapid pointing to invisible landmarks in a previously learned scene). In the adaptation phase, visual feedback was additionally provided after the turn and pointing task (display of an orientation that differed from the actual turning angle by a factor of 2). The results show that the natural, unadapted gain of perceived versus real turn angle in the pre-test was increased by nearly a factor of 2 in the adaptation phase and remained at this level during the post-test. We emphasise that at no point was simultaneous visual and vestibular stimulation provided. We conclude that vestibularly driven reflex-like spatial updating can be adapted without any concurrent sensory conflict, just by a pure cognitive conflict. That is, the cognitive discrepancy between the vestibularly updated reference frame (which served for the pointing) and the subsequently received static visual feedback was able to recalibrate the interpretation of self-motion.[Supported by Max Planck Society and Deutsche Forschungsgemeinschaft (SFB 550).]
Keywords: Riecke; Riecke_2003; bernhard-riecke; iSpaceWeb; posterWithoutPaper; spatial updating; talkWithoutPaper